2018
DOI: 10.1016/j.ejmg.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Desmosterolosis presenting with multiple congenital anomalies

Abstract: Desmosterolosis is a rare multiple congenital anomaly syndrome caused by a defect in the enzyme 3-beta-hydroxysterol delta-24-reductase (DHCR24) in the cholesterol biosynthesis pathway. Defects in this enzyme cause increased level of the cholesterol precursor desmosterol while disrupting development of cholesterol, impacting embryogenesis. A total of 9 cases of desmosterolosis have been reported to date. We report a 20-month-old male from consanguineous parents with multiple congenital anomalies including corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…In contrast, HDL-C is not associated with CVD risk in statin-treated patients after adjustment for additional lipoprotein parameters [144]. MESA also found that HDL-P is a significant predictor of incident CVD events and carotid intima-media thickening (cIMT), even adjusting for HDL-C levels and other CVD confounders [145]. In addition, HDL-P is an independent predictor of major adverse cardiovascular events (MACE) among patients undergoing angiography [146].…”
Section: Hdl-p Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, HDL-C is not associated with CVD risk in statin-treated patients after adjustment for additional lipoprotein parameters [144]. MESA also found that HDL-P is a significant predictor of incident CVD events and carotid intima-media thickening (cIMT), even adjusting for HDL-C levels and other CVD confounders [145]. In addition, HDL-P is an independent predictor of major adverse cardiovascular events (MACE) among patients undergoing angiography [146].…”
Section: Hdl-p Measurementmentioning
confidence: 99%
“…Experimental studies pointed out that the widely used measurements of HDL-C levels may have obvious limitations, and the quantitative evaluation of HDL-P might be a more robust biomarker for assessing HDL functions and predicting CVD risk [11,140]. A number of epidemiological and clinical trials, including the Heart Protection Study (HPS) [143], the Justification for the Use of Statins in Prevention: An Intervention Trial Evaluating Rosuvastatin (JUPITER) [144], and the Multi-Ethnic Study of Atherosclerosis (MESA) [145], demonstrated that HDL-P is a stronger and more independent predictor of CVD risk than HDL-C. In JUPITER study, investigators evaluated the relationship of HDL-C and HDL-P in more than 10,000 subjects with CVD risk.…”
Section: Hdl-p Measurementmentioning
confidence: 99%
“…While first described in 1998, the molecular mechanisms of desmosterolosis were not characterised until 2001 [140,141]. To date, only nine cases have been reported and clinical features include SLOS-like dysmorphism, thick alveolar ridges, gingival nodules, cleft palate, short limbs, severe congenital heart defect, atherosclerosis, arthrogryposis, ambiguous genitalia, microcephaly, agenesis of the corpus callosum, global developmental delay and intellectual impairment [141][142][143][144][145][146][147]. The diagnosis of desmosterolosis is made by demonstrating elevated levels of desmosterol by GC-MS analysis, with serum cholesterol levels usually normal [141,142].…”
Section: Desmosterolosismentioning
confidence: 99%
“…Although endogenous cholesterol biosynthesis is lost, the affected individuals are still exposed to some cholesterol via maternal-fetal transfer in utero and subsequently from dietary sources after birth ( 9 ). Desmosterolosis is a very rare disease, with only nine published cases, and has an estimated incidence of <1:10,000,000, compared with Smith-Lemli-Opitz syndrome with an observed incidence of 1:20,000 to 60,000 ( 6 , 10 , 11 ). Patients with desmosterolosis manifest a spectrum of defects affecting craniofacial and neurological development, intellectual disability, and developmental delays, with the most severe cases dying shortly after birth ( 8 , 12 , 13 , 14 , 15 , 16 ).…”
mentioning
confidence: 99%